The hard sell of paradise : Hawai'i, Hollywood, tourism - Sperb, Jason, 1978- (SUNY series, horizons of cinema., 2022)
"Traces the complex and contradictory representations of Hawai'i in popular film and television programs from the 1930s to the 1970s"--